Leading Managing Transformation to Digital University in Indonesian Context - Anggoro, Sigit; Nurdin, Diding; Sururi, Sururi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to analyze the management of digital transformation in the context of Indonesian universities. The explanatory research was employed, utilizing a survey questionnaire administered to a randomly selected sample of 302 individuals comprising members of the ICT alignment team, change team, staff, and lecturers within the PTS environment in the LLDIKTI IV area, Banten & West Java provinces. The data analysis in this study employed covariance-based structural equation modeling (SEM) procedures. Findings from this research indicate that achieving a radical transformation from traditional campus settings to digitalization, while adopting an incremental approach towards a smart university necessitates effective leadership and cultural support. A leadership coalition capable of institutionalizing new values, which subsequently become norms and guide the organizational culture, empowers members and fosters motivation for change oversight and participation. Ultimately, successful change management towards a smart university relies on leadership and culture, collectively institutionalized as a shared mental program, thereby shaping the meaningful trajectory towards a smart university.